ANALISIS FAKTOR PEMILIHAN LOKASI USAHA JASA PADA UMKM DI KECAMATAN PACIRAN - Ariffa Tio Hanggita (Manajemen Bisnis, 2018)
The aim of this study was to examine the most considered factor in selecting business place for Small and Medium Business Scale Empowerment (UMKM) in Paciran. The data were analyzed by using factor analysis. The results of the study showed that there were 3 considered factors in selecting business place, namely human resources & tax, power, and access. Based on factor analysis, the most considered factor in selecting business place in Paciran was human resources & tax (34.278%).